Insecticide applications with trunk injection method for reducing the damage level of Leptoglossus occidentalis (Heidemann, 1910) in stone pine stands - Sarikaya, O.; Parlak, S.; Yıldız, Yafes; Gencal, T.; Ozcankaya, I. M.; Selek, F.; Acici, O.; Yıldız, Yafes (Al-Farabi Kazakh Natl Univ, 2024)
Leptoglossus occidentalis was first detected in Turkey in 2009. The pest's damage to stone pine trees and its effects on seeds cause economic losses. In recent years, observations and predictions show that there is a significant threat not only to stone pine but also to other coniferous forests throughout country. In this study, pesticides were applied by trunk injection method in the experiment areas taken in stone pine stands of Bergama - Kozak region. In the systemic application carried out in 2020 and 2021, the Arborjet system was used and the insecticide with the active ingredient Azadirachtin (0.3 g/Lt) was used as an organic insecticide, as well as pesticide with the active ingredient Imidacloprid (200 g/Lt). In 2020, the highest seed filling rate was achieved after systemic Imidacloprid insecticide application with the Arborjet system. As a result of this application, the full seed rate reached 70.7% in Asagicuma, while this rate was 63.6% in the Karaveliler. The seed occupancy rate obtained from control trees in the Asagicuma was 37.96% and this rate reached 70.7% after systemic Imidacloprid application in the same field. Similarly, in the studies carried out in Asagicuma and Yukaribey experiment sites in 2021, only 35% of the seeds were filled in the cones taken from control trees, while the occupancy rate in the cones without insecticide application in the Yukaribey was determined to be 32.76%. In both trial sites, the highest seed fill rate was achieved after systemic Imidacloprid insecticide application with the Arborjet system. As a result of this application, the filled seed rate reached 67.89% in the Asagicuma and 69.86% in Yukaribey experiment sites.
Keywords: Leptoglossus Occidentalis; Pine Seeds; Trunk Injection; Pesticides; Turkey